Identification of Komo Skipjack Tuna (Euthynnus affinis) Fishing Areas Using Fish Aggregating Devices in the Waters of Werain Village, Selaru District, Tanimbar Islands Regency (Agrikan Jurnal Agribisnis Perikanan, 2024)
Komo tuna (pelagic) has a vertical and horizontal distribution area with groups that are caught using fishing rods. The study aims to describe the DPI using FADs, analyze the size distribution of fish caught in FADs. The study was conducted in September-October 2024 in the waters of Werain Village, KKT. Data were collected through DPI surveys, position mapping, FAD placement and FAD observations by catching, the catch was measured TL, analyzed descriptively displayed in the form of tables and images, making maps using ArcGIS and Struges for the size of the catch. The results of the study found seven DPIs and two locations that often catch and FADs were placed in the area. Cork FADs with a height of 1.40 cm and a diameter of 44 cm, attractors using 9 coconut leaves for one FAD, 70 kg attractor weights and 150 kg FAD weights made of cement concrete, 14 mill PE FAD ropes with a length of 200 m. The catch results of FADs in the first survey were 17 individuals, the second 21 individuals and the third survey 21 individuals with a length size of 29.7-37 cm TL. The presence presentation showed that the size of 32-34 cm dominated, namely 54.688%, already mature gonads.
Keywords: DPI; Komo Tuna; Fish Aggregating Devices; Tanimbar Islands